(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
This article modern budget reforms, which provide for the transition from “cost management” to “results management”, are aimed at improving and increasing the efficiency of financial management both at the regional and municipal levels. Local budgets, being the financial basis of local governments, play an important role in improving the social well-being of the population and economic development. However, ensuring a high level and quality of life of the population, sustainable economic growth, the development of the social sphere and the achievement of high socio-economic indicators of the development of the municipality require effective management of its budget.